Relation between sexual function, perceived social support, and adherence to treatment with infertility factor in women: A cross-sectional study - Marzie Sheikhian; Marzeyeh Loripoor; Zohreh Ghorashi; Faranak Safdari-Dehcheshmeh (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: In some societies, childbearing is a part of women's identity and infertile women are under a great amount of pressure from others. Objective: This study aims to evaluate the relationship between infertility factors and sexual functioning, perceived social support, and adherence to treatment in infertile women. Materials and Methods: In this cross-sectional study, 230 infertile women who referred to the infertility center of Shahrekord, Iran in 2022 were enrolled. Data were collected using demographic characteristics checklist, female sexual function index, multidimensional scale of perceived social support, and general adherence scale. Results: No significant relation was observed between the infertility factor and the mean score of sexual function, the mean score of perceived social support, and the mean score of adherence to treatment (p > 0.05). Among the aspects of sexual functioning, only the mean score of lubrication in the group of male factors was significantly higher than the common factors for men and women (p = 0.07). A linear positive relation was observed between sexual functioning (r = 0.189), perceived social support (r = 0.200), and adherence to treatment (r = 0.146) in infertile women. Conclusion: By providing proper training and counseling to infertile couples, we can improve their social support and sexual function so that they can complete their infertility treatment as a result.